A systematic assessment of Leporinus tigrinus (Characiformes: Anostomidae) using morphological and molecular data - Boaretto, Mariana Pascoal; Souza-Shibatta, Lenice; Birindelli, José L. O. (Zootaxa, 2024)
Leporinus tigrinus was described based on specimens collected in the rio Tocantins basin, and was only recently recorded at the rio Xingu, rio Tapajós and upper rio Paraná basins. So far, no study has compared specimens of all these distinct drainages focusing on understanding whether all these populations truly belong to a single species or may consist instead in a species complex. Our study focused on investigating the intraspecific variation within Leporinus tigrinus using morphological and molecular data. Both morphology and molecular analyses support that all samples belong to a single species widespread in the rio Araguaia, rio Tocantins, rio Xingu and rio Tapajós. In addition, the population occurring at upper rio Paraná is considered to be allochthonous, originating from the rio Araguaia/Tocantins. A comprehensive morphological description of the species, including osteological illustrations and descriptions are provided, as well as a comparative diagnosis with similar-looking species.